Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1016/s0014-5793(02)03504-4
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of the RSC nucleosome‐remodeling complex is important for the cells to tolerate DNA damage in Saccharomyces cerevisiae

Abstract: The essential Nps1p/Sth1p is a catalytic subunit of the nucleosome-remodeling complex, RSC, of Saccharomyces cerevisiae that can alter nucleosome structure by using the energy of ATP hydrolysis. Besides the ATPase domain, Nps1p harbors the bromodomain, of which the function (s) have not yet been de¢ned. We have isolated a temperature-sensitive mutant allele of NPS1, nps1-13, which has amino acid substitutions within the bromodomain. This mutation perturbed the interaction between the RSC components and enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 31 publications
4
37
0
Order By: Relevance
“…Indeed, mutations in the Rsc1, Rsc2 and Sth1 subunits of the yeast RSC complex, a member of the SWI/SNF class of remodelers, render cells hypersensitive to DNA break-inducing agents. [14][15][16] As for INO80, mutations in RSC subunits did not lead to misregulation of DNA repair genes or defects in checkpoint activation, 14,17 implicating RSC directly in DNA repair. Moreover, like Ino80, the RSC subunit Rsc8 and the catalytic subunit Sth1, were shown to be recruited to an HO-induced DSB.…”
Section: Evidence For Chromatin Remodelers At Dsbsmentioning
confidence: 94%
“…Indeed, mutations in the Rsc1, Rsc2 and Sth1 subunits of the yeast RSC complex, a member of the SWI/SNF class of remodelers, render cells hypersensitive to DNA break-inducing agents. [14][15][16] As for INO80, mutations in RSC subunits did not lead to misregulation of DNA repair genes or defects in checkpoint activation, 14,17 implicating RSC directly in DNA repair. Moreover, like Ino80, the RSC subunit Rsc8 and the catalytic subunit Sth1, were shown to be recruited to an HO-induced DSB.…”
Section: Evidence For Chromatin Remodelers At Dsbsmentioning
confidence: 94%
“…RSC rsc1 and rsc2 Saccharomyces cerevisiae mutants are sensitive to gamma irradiation [40], and to radiomimetics, alkylating agents and UV when grown at their semipermissive temperatures [43][44][45]. SWI/SNF snf5 and snf2 Saccharomyces cerevisiae mutants are sensitive to radiomimetics and are moderately sensitive to alkylating agents and UV irradiation [45].…”
Section: Asf1mentioning
confidence: 99%
“…59 Again, it has been shown that mutations in the subunits of the Swi/Snf and RSC remodeling complexes result in hypersensitivity to agents that induce DSBs. [58][59][60][61] Overall, the role of chromatin remodelers in transcription (essentially their function in altering the topology of chromatin and increasing DNA accessibility) has predominantly been used as a basis to speculate on the function of these complexes in the DSB response pathway. Although intuitively this seems correct, further research is required to confidently assign specific roles for these chromatin-remodeling complexes in the context of DSB repair.…”
Section: Chromatin Remodeling Complexes Are Involved In Double-strandmentioning
confidence: 99%